Comprehensive reconstruction and rehabilitation of explosive hand trauma: a case report - Jabre, Stephane; Maroun, Jose; Kazzi, Alexandre El; Kazzi , Wissam El (International Journal of Research in Orthopaedics, 2025)
Firework-related hand injuries can be devastating, resulting from a combination of blast forces, thermal impact, and penetrating trauma. These injuries result in extensive soft tissue damage, fractures, and partial or complete amputations, thereby posing complex challenges for surgical management and rehabilitation. We report the case of a 23-year-old male technician who sustained a severe explosive hand injury from fireworks. Initial treatment focused on thorough wound irrigation, debridement, skeletal stabilization, and prompt initiation of prophylactic antibiotics. Multiple staged procedures were performed, including open reduction and internal fixation of carpometacarpal dislocations, nerve and tendon repairs, and flap reconstructions to restore soft tissue integrity. Despite the complexity and extent of the injury, a staged approach facilitated optimal wound healing and partial functional restoration of the hand. This case underscores the multifaceted nature of blast-related hand injuries, where extensive tissue damage, compromised vascularity, and contamination necessitate a multidisciplinary approach. The hand surgery team collaborated to ensure appropriate skeletal stabilization, nerve and tendon repair, and soft tissue coverage. Early and intensive rehabilitation, encompassing both physical and psychological support, was critical in optimizing recovery. Although functional limitations persisted, the combination of modern surgical techniques and structured rehabilitation yielded a satisfactory outcome relative to injury severity. Successful management of severe hand trauma from fireworks requires coordinated, staged surgical interventions, and comprehensive rehabilitation. While advances in reconstructive surgery improve outcomes, complete recovery may remain elusive in profound blast injuries. Public awareness and preventive measures are paramount to reducing the incidence of such injuries.